CD8 T cells contribute to lacrimal gland pathology in the nonobese diabetic mouse model of Sjögren syndrome. Issue 8 (23rd May 2017) - Barr, Jennifer Y; Wang, Xiaofang; Meyerholz, David K; Lieberman, Scott M
Abstract : Sjögren syndrome is an autoimmune disease characterized by targeted destruction of the lacrimal and salivary glands resulting in symptoms of severe ocular and oral dryness. Despite its prevalence, the mechanisms driving autoimmune manifestations are unclear. In patients and in the nonobese diabetic (NOD) mouse model of Sjögren syndrome, lymphocytic infiltrates consist of CD4 and CD8 T cells, although the role of CD8 T cells in disease pathogenesis has been largely unexplored. Here, we evaluated the contribution of CD8 T cells to lacrimal and salivary gland autoimmunity. Within the lacrimal and salivary glands of NOD mice, CD8 T cells were proliferating, expressed an activated phenotype, and produced inflammatory cytokines. Transfer of purified CD8 T cells isolated from the cervical lymph nodes (LNs) of NOD mice into NOD‐severe combined immunodeficiency recipients resulted in inflammation of the lacrimal glands, but was not sufficient to cause inflammation of the salivary glands. Lacrimal gland‐infiltrating CD8 T cells displayed a cytotoxic phenotype, and epithelial cell damage in the lacrimal glands was observed in recipients of CD8 T cells regardless of the presence of CD4 T cells. Collectively, our results demonstrate that CD8 T cells have a pathogenic role in lacrimal gland autoimmunity. The gland‐specific pathogenicity of CD8 T cells makes them a valuable resource to further understand the mechanisms that discriminate lacrimal versus salivary gland autoimmunity and for the development of new therapeutics that target the early stages of disease.